2020
DOI: 10.1155/2020/8894257
|View full text |Cite
|
Sign up to set email alerts
|

Jian‐Pi‐Yi‐Shen Regulates EPO and Iron Recycling Protein Expressions in Anemic Rats with Chronic Kidney Disease: Accumulation of Hypoxia Inducible Factor‐2α via ERK Signaling

Abstract: Jian-Pi-Yi-Shen (JPYS), the traditional Chinese medicine (TCM) decoction, has been commonly used to treat chronic kidney disease (CKD) and its complications such as anemia. JPYS has been previously found to induce erythropoietin (EPO) production in HEK293T cells and CKD rats. However, the mechanism of JPYS in treating anemia of CKD rats has remained largely unknown. Here, we further extend our effort to investigate the translational control of hypoxia inducible factor- (HIF-) α protein via ERK signaling and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Human gene HBB codes for hemoglobin subunit β, whose deficit (thalassemia) worsens women’s reproductive health [ 81 ], in agreement with the direction of expression change of the dog orthologous gene—deficit during microevolution [ 28 ] ( Table 4 ). Conversely, in traditional Chinese medicine, the Jian-Pi-Yi-Sheng decoction (JPYS) is employed to raise the HBB level for treating anemia in chronic kidney diseases [ 82 ]…”
Section: Resultsmentioning
confidence: 99%
“…Human gene HBB codes for hemoglobin subunit β, whose deficit (thalassemia) worsens women’s reproductive health [ 81 ], in agreement with the direction of expression change of the dog orthologous gene—deficit during microevolution [ 28 ] ( Table 4 ). Conversely, in traditional Chinese medicine, the Jian-Pi-Yi-Sheng decoction (JPYS) is employed to raise the HBB level for treating anemia in chronic kidney diseases [ 82 ]…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, three HIF-α prolyl hydroxylases can initiate proteasomal degradation of HIF-α, thereby suppressing EPO production [19]. It has been demonstrated that a Chinese herbal formulation (Jian Pi Yi Shen) stimulates HIF-2α and EPO protein expression in both the kidney and liver of rats with chronic kidney disease [20]. A novel HIF prolyl hydroxylase inhibitor (TP0463518) was found to induce dose-dependent EPO production from the liver in healthy volunteers and in patients with chronic kidney disease [21].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Jianpi Yishen Tang (JPYST) is a traditional Chinese medicine compound commonly used to treat chronic kidney diseases along with its complications [ 16 21 ]. In our previous studies, it was observed that JPYST protects 5/6 nephrectomized rat kidney from damage via suppression of inflammatory responses by inhibiting the NF- κ B activation and mediating downregulation of proinflammatory mediators in vitro [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%